THE SPECIFICITY OF THE FEMALE ANTHROPONYMICON IN A. PLATONOV'S NOVEL "CHEVENGUR" (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-2-29-40The semantic potential of female anthroponyms in A. Platonov's novel “Chevengur” is considered. It is obvious that the choice of one or another onym as a nomination of a character is always determined directly by the author's associations associated with this or that name. It was revealed that the name is one of the ways to recognize the hero, since it indicates belonging to a specific time, historical events, and society. The anthroponymicon of A. Platonov's novel serves to demonstrate the most important meanings of the writer's images, revealing his individual author's picture of the world.Key words: A. Platonov, “Chevengur”, onym, anthroponym, semantic potential